Explaining New Models of Global Voluntary Regulation: What Can Organisational Studies Contribute?. Issue 1 (14th February 2018) - Marx, Axel; Wouters, Jan
Abstract: Global governance in its myriad forms and actor constellations has decisively demonstrated the potential for rule‐making above the nation state to be liberated from the 'iron cage' of traditional intergovernmental forums and multilateral bureaucracy. To further investigate an increasingly complex global reality, we propose drawing on organisational theories and methods for penetrating the internal dynamics of global governance processes and outcomes. This article begins by mapping out the current use of organisational theories in global governance research. It then turns to exploring the potential for other areas of organisational theory and conceptual development to shed light on the governance dynamics and performance of voluntary sustainability standards (VSS), a significant site of transnational rule‐making and experimentation by private actors. We highlight a paradigmatic shift from 'arms‐length' to 'embedded' models of VSS monitoring and regulation, reflected in new modes of engagement and interaction between rule‐makers and rule‐takers. This new generation of embedded VSS governance is distinguishable by enhanced information provision, learning and knowledge creation. The implications of embedded governance for VSS monitoring and performance are explored with reference to the experience of the Fair Wear Foundation (FWF). Abstract : In sum, we warmly support Coen and Pegram's call for diverse disciplinary perspectives to be brought to bear on the study of global governance.